The Future of Museums and Digital Transformation Challenges - Carvalho, Ana (2021)
[ENG] In this chapter Carvalho (with Alexandre Matos, Universidade do Porto) propose that museum planning for digital transformation, along with strong leadership remain crucial to establishing strategic guidelines and objectives. This not only involves establishing a new mind-set, organizational transformation, the inputs of new knowledge and competences, but also assessing the effort and resources (skilled people, IT infrastructure, money and time) required going forward. This chapter was also significant by pinpointing some of the ethical challenges related to digital transformation (e.g. protection of personal data and privacy, open access to museum collections vs copyright constraints, open access vs loss of income, museums and control of data, and social media). [PT] Neste capítulo propomos que o planeamento dos museus para a transformação digital, a par com lideranças sólidas são aspectos cruciais para o estabelecimento de objectivos estratégicos. Neste contexto, considera-se a necessidade de reflectir sobre uma mudança de mentalidades, com impacto na forma como os museus se organizam, a introdução de novos conhecimentos e competências, assim como atender ao esforço e aos recursos necessários (qualificação de pessoal, infraestrutura tecnológica e digital, investimento, tempo). Este capítulo foi também significativo ao problematizar algumas das questões éticas relacionadas com a transformação digital (ex. protecção de dados e privacidade; acesso aberto às colecções online vs constrangimentos de direitos de autor; acesso aberto vs perda de receitas; museus e controlo da informação; redes sociais).